Strengths and weaknesses aspects in marathon runners training - Paula, I.; Sabau, E.; Gheorghe, D. (Science, Movement & Health, 2021)
Problem statement:Running is a natural activity. Marathon is a track and field race that involves special physical and mental effort and less technical requirements. Marathon is the activity that connect body and mind in a whole effort. Marathon means a race of 42.195 km in relatively constant speed tempo. The effort support is mainly based on a strong and flexible locomotor system combined with heathy heart and lungs.As much important is a healthy diet that improve the performance:a diet strategy based on the principle "eating less but often", provides energy levels constant all the day. It is possible to appear some unpleasant aspects in training schedule. These can be in physical integrity, as: skin wounds, ankle or knees pain. The knee is the most frequently injured joint in runners at all distances. Foot and ankle injuries are the most common injuries supported by marathon runners.One of the most unpleasant pain training is plantar fasciitis as the result of irritation of the plantar fascia. So, the content of marathon runners training has to be carefully managed according to the strong and weak points. The aim of the research:The paper`s goal is to present some aspects that improve or limited the quality of marathon runners training. In this regard we try to identify the strengths and weaknesses points of these athletes. Conclusions:Nowadays more and more people are interested in marathon running. Besides the performance runner, ordinary people enjoy running in nature or on the cities` streets.In order to be healthy and have fun, it is important to know the strengths and weaknesses aspects of amateur or performance runner training.